Dynamics of Urban Expansion in the Northwest Mesoregion of Minas Gerais: Analysis and Trends with the Urban Expansion Index - Santos, Arthur Pereira dos; Arantes, Leticia Tondato; Toledo, Mayra Vanessa Lizcano; Américo-Pinheiro, Juliana Heloisa Pinê; Silva, Darllan Collins da Cunha e (National Journal of City Management, 2025)
Objective – To investigate the evolution of the Urban Expansion Index (UEI) in the Northwest mesoregion of Minas Gerais (MG), Brazil, between 1990 and 2020, using Remote Sensing (RS) data from the MapBiomas project.Methodology – The UEI was calculated based on the proportion of urbanized area in relation to other land use classes in each municipality. The values were normalized to enable temporal and spatial comparisons across municipalities and then classified into five urbanization categories. Spatial analysis was conducted through the creation of thematic maps, allowing a detailed visualization of urban growth trends and geospatial variations over time.Originality/relevance – The study provides a systematic approach to monitoring urban expansion at the regional scale, integrating RS data and spatial analysis with a focus on territorial management. It emphasizes the application of a specific index (UEI) and its spatial categorization to interpret urban dynamics.Results – The findings reveal significant variations in the level of urbanization among the 19 municipalities analyzed. Vazante recorded the highest UEI in 2020, followed by Paracatu and Unaí, indicating substantial urban growth. In contrast, Formoso and Guarda-Mor maintained the lowest levels of urbanization, reflecting limited urban development. The data suggest that economic factors such as agriculture, mining, and infrastructure investments influence urbanization patterns in the region.Theoretical/methodological contributions – The application of the UEI and the use of MapBiomas data demonstrate the effectiveness of Remote Sensing in analyzing regional urban expansion. The study contributes methodologically by proposing a useful tool for comparative analysis and territorial planning.Social and environmental contributions – The results underscore the importance of using RS data to support public policy formulation aimed at urban planning and the promotion of sustainable urban development, tailored to the local characteristics of the Northwest mesoregion of Minas Gerais.
Keywords: Territorial Management; Remote Sensing; Sustainable Urban Development